Chemical constituents from the fruits of Ligustrum japonicum and their inhibitory effects on T cell activation. (September 2017) - Ngo, Quynh-Mai Thi; Lee, Hyun-Su; Nguyen, Van Thu; Kim, Jeong Ah; Woo, Mi Hee; Min, Byung Sun
Abstract: A previously undescribed nor-dammarane, 3 β, 20, 23-trihydroxy-24, 25, 26, 27-tetranordammarane; three previously undescribed secoiridoid glycosides, ligujaponosides A–B, and iso-oleonuzhenide; and twenty three known compounds, were isolated from the fruits of Ligustrum japonicum Thunb. Their chemical structures were elucidated by extensive spectroscopic analyses, including 1D and 2D NMR, and HRMS. The isolated compounds were screened for immunosuppressive effects on T activated cells by evaluating interleukin-2 (IL-2) production. Among them, sesamin inhibited IL-2 production in Jurkat T cells with an IC50 value of 38 ± 2 μM. In addition, sesamin inhibited the phosphorylation of extracellular signal-regulated protein kinase (ERK), a member of the mitogen-activated protein kinase (MAPK) family, in phorbol 12-myristate 13-acetate (PMA)/A23187-stimulated T cells. Therefore, sesamin was demonstrated to inhibit T cell activation via regulation of MAPK phosphorylation pathway. Graphical abstract: Highlights: 27 compounds were isolated from Ligustrum japonicum. One nor-dammarane and three secoiridoid glycosides were elucidated by spectroscopic analyses. 3 compounds, including sesamin, exerted inhibition on T cell activation.